FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN QUICK RESPONSE INDONESIAN STANDARD (QRIS) BANK SYARIAH DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL 3 - Rifaatul Indana; Khallimatus Sya’diah (Program Studi Ekonomi Syariah, 2023)
Digitalization has encouraged Bank Indonesia to develop an integrated payment system infrastructure, namely QRIS, so that transactions are easier, faster, and secure. This study aims to determine interest in using QRIS with approach Technologi Acceptance Model 3. The population of this study is generation Z who live in Yogyakarta. This study obtained a sample that fits the criteria of 100 respondents. The results of data collection are then processed using the SmartPLS 4.0 application. Based on the test results, it shows that almost all variables have a positive and significant effect, except for the subjective norm variable which does not have a significant effect on perceived usefulness